Fibrous histiocytoma in a nine week old male infant. - O’Hagan, A.H.; Irvine, A.D.; Brennan, T.; Walsh, M.Y.; Bingham, E.A. (European Journal of Pediatric Dermatology, 2001)
Fibrous histiocytoma is a rare tumour seen most commonly in infants. The majority of cases are clinically benign. We report a 12-day-old male infant with a fibrous histiocytoma in the right nasolabial fold. We discuss the clinical and histopathological features of this case and the difficult management issues raised by this lesion. We also discuss the wider differential diagnosis of the facial cherry red spot in infants and children.